The Relationship Between the Patent-holder and Developing Nations: Overcoming the Consequences of Intellectual Property Rights - Galin-Corini, Laura Maria (Glendon Journal of International Studies, 2017)
Abstract: Disease is spreading at a faster rate than ever before. Our globalized world is faced with the constant threat of devastating pandemics due to the increase in frequency, intensity and distance with which humans and goods are capable of traveling. Technology, information and resources, which play a crucial role in the prevention, management and eradication of disease, are theoretically more accessible in today’s world in terms of their ability to be effectively transported to the most remote regions of our planet. However, the international agreements and policies currently in place create barriers, preventing the achievement of a higher standard of global health. One such obstacle emerges as a result of Intellectual Property Rights (IPRs). On the one hand, these ownership rights acknowledge and compensate scientists for their innovations; this encourages further development of medication. Nevertheless, these rights make drugs unaffordable and inaccessible to citizens of the Global South. IPRs fail to recognize the knowledge of indigenous people, whose ancient herbal medicines often-times inspire the innovations. In doing so, IPRs breed increasing mistrust and tension on the part of those in the Global South towards the Global North. This article provides a case study and possible amendments to Intellectual Property policies with the intension of facilitating trust between communities, establishing a more efficient system of resource distribution, increasing the global standard of living through better healthcare management, and consequently, creating a more stable and safe world. Résumé : La maladie se propage à un rythme plus rapide que par le passé. Notre monde globalisé est confronté à la menace constante de pandémies ravageuses en raison de l’augmentation de la fréquence, de l’intensité et de la distance que les êtres humaines et les biens sont capables de voyager. La technologie, l’information et les ressources, qui jouent un rôle critique dans la prévention, la gestion et l’éradication de la maladie sont, en théorie, plus accessible dans le monde d’aujourd’hui quant à leur capacité d’être transporté efficacement aux régions les plus éloignées de la planète. Cependant, les accords internationaux et les politiques en place actuellement créent des barrières qui empêchent la réalisation d’un niveau plus élevé de santé globale. Un tel obstacle émerge du fait de les Droits de Propriétés Intellectuelles (DPI). D’une part, ces droits à la propriété reconnaissent et récompensent les scientifiques pour les innovations ; ceci encourage le développement d’autres médicaments. Néanmoins, ces droits rendent les traitements inabordables et inaccessibles aux citoyens du Sud Global. Les DPS ne reconnaissent pas les savoirs des peuples autochtones, dont les médicaments anciens à bases des plantes sont souvent source d’inspiration pour les innovations. Ce faisant, les DPS alimente une méfiance et tension de part de ceux et celles dans le Sud Global envers le Nord Global. Cet article offre une étude de cas et propose des modifications éventuelles aux politiques de la Propriété Intellectuelle avec l’objectif de faciliter la confiance entre les communautés, d’établir un système de distribution de ressources plus efficaces, d’améliorer le niveau de vie mondial par une meilleure gestion des systèmes de santé et ainsi, de créer un monde plus stable et plus en sécurité.